Identifikasi Aktivitas Biologis, Prediksi Toksisitas, dan Molecular Docking Senyawa Jubanine dari Tanaman Bidara Arab sebagai Kandidat Antivirus SARS-CoV-2 - Fakih, Taufik Muhammad; Putri, Nawang Wulan Rachmatillah Prastowo; Marillia, Viola; Ramadhan, Dwi Syah Fitra; Darusman, Fitrianti (Jurnal Riset Kimia, 2022)
Coronavirus disease (COVID-19) is a disease of the respiratory tract caused by the coronavirus (SARS-CoV-2). Jubanine A, jubanine B, jubanine C, jubanine G, and jubanine H compounds in the arabian bidara plant (Ziziphus spina-christi L.) are known to treat viral and bacterial infections. The purpose of this study was to test the affinity of the compounds jubanine A, jubanine B, jubanine C, jubanine G, and jubanine H in the arabian bidara plant to the non-structural protein 15 (Nsp15) receptor. This research was carried out by identifying the physicochemical properties of the test compounds using the swissADME server. After that, geometry optimization was performed using the Quantum ESPRESSO 6.6 software, then macromolecule preparation was accomplished using the BIOVIA Discovery Studio 2020 software. Furthermore, method validation and molecular docking simulations were demonstrated using MGLTools 1.5.6 software with AutoDock Tools 4.2. Then the analysis of the molecular docking results was carried out using the BIOVIA Discovery Studio 2020 software. Finally, the toxicity of the test compound was predicted using the Toxtree 3.1.0 software. Based on the results of free binding energy (âˆ†G), jubanine H has the best affinity among the other five compounds with the lowest binding energy value of âˆ’6.51 kcal/mol.